1)
a) 6x^2-3x=0
3x(2x-1)=0
x=0; x=1/2
б)25x^2=1
x^2=1/25
x=±√1/25
x=1/5;x=-1/5
в)4x^2+7x-2=0
D=49+32=81
x=(-7±√81)/8
x=-2; x=1/4
г)4x^2+20x+25=0
D=400-400=0
X=-20/8
x= -5/2
д)3x^2+2x+1=0
D=4-12=-8<0
x∈∅
е)(x^2+5x)/2-3=0
(x^2+5x)/2=3
x^2+5x=6
x^2+5x-6=0
x=1; x=-6
2) x^4-29x^2+100=0
Замена:t=x^2, t>=0
t^2-29t+100=0
D=841-400=441=21^2
t=25; t =4
⇒x=±√25; x=±√4;
x=-5;x=5;x=-2;x=2
3)(3x^2+7x-6)/(4-9x^2)
Решим отдельно уравнение в числителе
3x^2+7x-6=0
D=49+72=121=11^2
x=-3;
x=2/3
⇒3x^2+7x-6=(x+3)(3x-2)
(x+3)(3x-2)/(2-3x)(2+3x) = -(x+3)/(2+3x)
4) x^2-26x+q=0
По теореме Виета
x1+x2=26
12+x2=26
x2=14
x1*x2=q
14*12=q
q=168
1.
1)
38² - 64 = 38² - 8² = (38 - 8)(38 +8) = 30 * 46 = 1380,
2.
1)
2в² - 18 = 2 * (в² - 9) = 2 * (в - 3)(в + 3),
3)
81х² - 18ху + у² + 63х - 7у = (81х² - 18ху + у²) + (63х - 7у) =
= (9х - у)² + 7*(9х - у) = (9х - у)(9х - у + 7),
4)
m² + n² + 2mn = (m + n)².
3.
а)
(8 - 2n)(8 + 2n) + (9 + 2n)² - 64 = 64 - 4n² + 81 + 36n + 4n² - 64 =
= 36n + 81 = 9(4n + 9),
б)
(3х - 8)² + (4х - 8)(4х + 8) = 9х² - 48х + 64 + 16х² - 64 = 25х² - 48х,
при х=-2:
25 * (-2)² - 48 * (-2) = 100 + 96 = 196,
4.
1 число - х,
2 число - (х+2),
(х+2)² - х² = 188,
х² + 4х + 4 - х² = 188,
4х = 184,
х = 46 - 1 число,
х+2 = 46+2 = 48 - 2 число